Programming Effects of Maternal Nutrition on Intestinal Development and Microorganisms of Offspring: A Review on Pigs - Liang Hu; Fali Wu; Lianqiang Che (Microorganisms)
Intestinal development is a critical determinant of growth and overall health in pigs. Accumulating evidence underscores the significant influence of intestinal microbiota on essential physiological functions and systemic health. Dietary nutrients play a pivotal role in regulating both intestinal development and the composition of intestinal microbiota. Optimal early-life nutrient provision ensures proper intestinal growth and functional maturation, with maternal nutrition emerging as a key factor shaping intestinal development during fetal and neonatal stages. This review synthesizes recent studies on maternal nutrient intake—encompassing protein, energy, carbohydrates, minerals, vitamins, probiotics, and prebiotics—and their effects on intestinal growth and health of offspring. Emerging multi-omics evidence has revealed that gestational and lactational nutrition dynamically coordinates offspring intestinal development through vertical microbial transmission and epigenetic mechanisms, such as DNA methylation and histone acetylation. These processes further regulate intestinal barrier maturation, mucosal immunity, and enteroendocrine signaling. Collectively, this review emphasizes that enhancing maternal nutrition can promote postnatal growth by enhancing intestinal development and early microbial colonization in piglets. Further research is crucial to determining the optimal nutritional strategies during the perinatal period.